Biochemical, structural characterization and in-vitro evaluation of antioxidant, antibacterial, cytotoxic, and antidiabetic activities of nanosuspensions of Cinnamomum zeylanicum bark extract - Nawaz, Aqsa; Ali, Tayyab; Naeem, Muhammad; Hussain, Fatma; Li, Zhiye; Nasir, Abdul (Frontiers in Chemistry, 2023)
Cinnamomum zeylanicum is a traditional medicinal plant known for its anti-inflammatory, antidiabetic, antimicrobial, anticancer, and antioxidant properties. Its therapeutic efficacy using nanosuspensions is still unclear for treating infectious diseases. This study was designed to evaluate the bioactivities, biochemical characterization, and bioavailability of freshly prepared nanosuspensions of Cinnamomum zeylanicum. Structural and biochemical characterization of C. zeylanicum and its biological activities, such as antioxidants, antimicrobials, antiglycation, α-amylase inhibition, and cytotoxicity was performed using Fourier-transform infrared (FTIR) spectroscopy and High-Performance Liquid Chromatography (HPLC). C. zeylanicum extract and nanosuspensions showed TPCs values of 341.88 and 39.51 mg GAE/100g while showing TFCs as 429.19 and 239.26 mg CE/100g, respectively. DPPH inhibition potential of C. zeylanicum extract and nanosuspension was 27.3% and 10.6%, respectively. Biofilm inhibition activity revealed that bark extract and nanosuspension showed excessive growth restraint against Escherichia coli, reaching 67.11% and 66.09%, respectively. The α-amylase inhibition assay of extract and nanosuspension was 39.3% and 6.3%, while the antiglycation activity of nanosuspension and extract was 42.14% and 53.76%, respectively. Extracts and nanosuspensions showed maximum hemolysis at 54.78 and 19.89, respectively. Results indicated that nanosuspensions possessed antidiabetic, antimicrobial, anticancer, and antioxidant properties. Further study, however, is needed to assess the clinical studies for the therapeutic use of nanosuspensions.